Implementation of Quiet Time for Noise Reduction on a Medical-Surgical Unit - Applebaum, Diane; Calo, Oriana; Neville, Kathleen (The Journal of nursing administration, 2016)
The objective of this evidence-based investigation is to determine the efficacy of a quiet-time intervention to reduce noise in the hospital setting. For many reasons, noise continues to increase in the hospital setting. In a descriptive comparative design, using a convenience sample of hospitalized patients, 80 patients were assessed on their perceptions of noise using the Patient Survey on Noise During Hospital Stay. Data revealed favorable responses to quiet time, with 70% of subjects reporting quiet-time intervention to be effective in reducing noise. Sixty percent of participants felt that 1 hour of quiet time helped to facilitate a quieter, more restful environment for the whole day. A quiet-time intervention is effective in addressing patient perception of noise while in the acute care hospital setting.